Future skilled-labour markets in Germany : from model-based calculations to scenarios - Helmrich, Robert [Verfasser]; Wolter, Marc Ingo [Verfasser]; Zika, Gerd [Verfasser]; Maier, Tobias [Verfasser] (My University, 2013)
"In this article, we focus on the potential development of the German labour market. For this purpose, we developed a forecasting system that considers both supply and demand by occupational fields and qualifications and that relies on consistent datasets, exogenous assumptions and systematic correlations. We present the key impacts for our forecasting system and highlight the effects of different assumptions (scenarios) exemplified on our demand model. On the supply side, we point out how different behaviours on the individual level influence the structure of development of the supply of skilled labour. Keeping the possibility of those various potential futures in mind, we conclude with an outlook on potential skilled labour shortages in the future." (Authors' abstract, IAB-Doku)
Keywords: G 1.2.1 Grund- & Strukturdaten des Arbeitsmarktes; G 1.2.3 Qualifikationsentwicklungen; S 6 Berufsbereiche; Arbeitsmarktentwicklung; Arbeitsmarktprognose; Arbeitskräftebedarf; Arbeitskräfteangebot; Qualifikationsniveau; Berufsfeld; Projektion